A case of vitamin D hydroxylation-deficient rickets type 1A caused by 2 novel pathogenic variants in gene - You-Min Kim; Yoon-Young Jang; Ji-Eun Jeong; Hye-Jin Park; Ja-Hyun Jang; Jin-Kyung Kim (Korean Society of Pediatric Endocrinology, 2019)
Vitamin D hydroxylation-deficient rickets type 1A (VDDR1A, OMIM 264700) is a rare autosomal recessive inherited disorder. Pathogenic variants in the CYP27B1 gene lead to loss of 1α-hydroxylase activity. We report the case of a 22-month-old toddler who presented with growth retardation and delayed development. The patient exhibited the typical laboratory findings of VDDR1A, including hypocalcemia (calcium: 5.2 mg/dL), elevated serum level of alkaline phosphatase (2,600 U/L), elevated serum level of intact-parathyroid hormone (238 pg/mL), low 1,25(OH)2D3 level (11.2 pg/mL), and normal 25(OH)D3 level (40.7 ng/mL). His height and weight were 76.5 cm and 9.5 kg, respectively (both <3rd percentile). The Bayley Scales of Infant and Toddler Development II indicated significantly delayed development (mental development index <50, psychomotor development index <50). The patient was a compound heterozygous for two novel pathogenic variants in the CYP27B1 gene: c.57_69del (p.Glu20Profs*2) and c.171dupG (p.Leu58Alafs*275), inherited from his mother and father, respectively. The patient showed remarkable improvement after treatment with calcitriol and calcium carbonate.